Sporotrichosis with Bone Involvement: An Alert to an Occupational Disease - Felipe de Carvalho Aguinaga; Beatriz Moritz Trope; Nurimar Conceição Fernandes; Delia Celser Engel; Marcia Ramos- (Karger Publishers, 2014)
Sporotrichosis is a subacute or chronic mycosis caused by a fungus of the genus Sporothrix, which is found in soil. It can be acquired by trauma to the skin. Bone and joint lesions are very rare. The city of Rio de Janeiro is undergoing an epidemic transmitted by cats, and this should be an alert for the risk to professionals in contact with these animals. The patient was a veterinarian who developed occupational sporotrichosis with osteoarticular involvement transmitted by a cat during a consultation.